Breast feeding in premature infants: an integrative review - Eveline Franco da Silva; Fernanda Muniz; Fátima Helena Cecchetto (Universidade Federal de Santa Maria, 2012)
Objective: to analyze the scientific production related to breast feeding in preterm births. Method: it is developed through an integrative review of the Scientific Electronic Library Online. It was included 12 articles from studies conducted in Brazil, published between 2000 and 2009. Results: the studies approached the importance of breast feeding in premature infants, the positive and negative influences for this practice and performance of professionals in this context. The highest incidence of publication was in 2004. On the authority revealed a greater amount of nurse's publication. Final considerations: the studies analyzed presented as recommendations or conclusions the importance of integrity, understanding the child, woman and family within their social context. It is suggested the development of exploratory studies on the subject to enable greater understanding of this practice and indicate strategies for health education in this context